Climate policy of Poltava and analysis of innovative methods of adaptation to climate changes in cities - Taranenko, A.; Hlazunova, V. (Scientific Progress & Innovations, 2022)
The issue of climate change is one of the most actual at the international level. These factors caused one of the most complex problems - atmospheric air pollution. The accumulation of greenhouse gases, dust, and other pollutants causes climate change and an increase in the average temperature on the planet. Therefore, today the main goals of humans are the fight against climate change, adaptation to environmental conditions, and creation of comfortable conditions for life on the planet.Modern cities should also be at the center of the climate change debate. After all, cities have a significant impact on the environment and a large number of people live in them, which requires comfortable living conditions. Therefore, the idea that cities should become more sustainable is becoming more and more widespread. The Paris Agreement, reached in 2015, highlighted the growing importance of cities in achieving global climate change goals. The main task of the modern city is to adapt to climate change, both by reducing emissions of greenhouse gases which contribute to a change in the global atmosphere and by ensuring their stability to the effects of climate change. Adaptation measures can be considered more economical and efficient than countermeasures, and their timely implementation leads to the emergence of additional opportunities and directs humans to better scenarios of development and life support on the planet. Climate policy and policy of adaptation to climate change in Poltava city are based on planning and creation of programs, action plans, and management decisions. The goals of the climate policy in Poltava city are the implementation of adaptation measures and reduce the susceptibility of the city's ecosystem to conditions of climate change. The main emphasis in the policy of adaptation to climate change is the issue of reducing emissions of greenhouse gases into the atmospheric air and landscaping of the city. Taking into account the experience of foreign and Ukrainian cities, and modern innovative achievements, the first step on the way to creating comfortable living conditions in Poltava city is the increasing of green spaces. Increasing the number of green zones, placing "green stops", "rain gardens", scientific selection, and combination of plants, and raising the level of environmental consciousness of the population will allow to significantly improve the microclimate of Poltava and adapt to climate changes.